AN ESTER OF 4-METHOXY CYNNAMIC ACID ISOLATED FROM Xylocarpus moluccencis (Lamk) M. Roem (MELIACEAE) - Tukiran Tukiran; Septiani Setyo Cahyasari; Kuniyoshi Shimizu (Indonesian Journal of Chemistry, 2012)
An ester derivative of 4-methoxycynnamic acid, i.e. 2-ethylhexyl 4-methoxy cynnamate was isolated for the first time from the chloroform extract of stem bark of Xylocarpus moluccencis (Lamk) M. Roem) (Meliaceae) along with β-sitosterol and stigmasterol. The first structure was elucidated with the help of various spectroscopic techniques, including IR, GC-MS, and NMR spectra. Two last structures were determined by comparison with the reported compounds in literature. These compounds were also found in the hexane extract of the plant.